Die Elfenbeinfunde aus Kehf-el-Baroud (Ziaïda, Ben Slimane, Marokko) und die Frage des Nordafrikanischen Elefanten - Banerjee, Arun; Mikdad, Abdeslam; Dindorf, Willi; Reichmann, Thomas; Schuhmacher, Thomas (Madrider Mitteilungen, 2020)
Zusammenfassung folgt.